2021
DOI: 10.1101/2021.08.20.21262158
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virological characteristics of SARS-CoV-2 vaccine breakthrough infections in health care workers

Abstract: BackgroundSARS-CoV-2 vaccines are highly effective at preventing COVID-19-related morbidity and mortality. As no vaccine is 100% effective, breakthrough infections are expected to occur.MethodsWe analyzed the virological characteristics of 161 vaccine breakthrough infections in a population of 24,706 vaccinated healthcare workers (HCWs), using RT-PCR and virus culture.ResultsThe delta variant (B.1.617.2) was identified in the majority of cases. Despite similar Ct-values, we demonstrate lower probability of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
43
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 25 publications
7
43
0
2
Order By: Relevance
“…For samples with Cn values below 27, we found that the probability of being viral culture positive was lower for samples coming from vaccinated individuals versus newly vaccinated and unvaccinated individuals. These data suggest that for a given viral genome load (as measured by RTqPCR), vaccinated individuals may be less infectious than unvaccinated individuals, consistent with a recent report examining Delta breakthrough infections 8 . However, we must emphasize that this difference is not statistically significant, potentially due to both the relatively small number of samples from vaccinees and the fact that only 6 out of 12 individuals included in the vaccinated group were fully vaccinated at the time of enrollment.…”
Section: Main Textsupporting
confidence: 88%
“…For samples with Cn values below 27, we found that the probability of being viral culture positive was lower for samples coming from vaccinated individuals versus newly vaccinated and unvaccinated individuals. These data suggest that for a given viral genome load (as measured by RTqPCR), vaccinated individuals may be less infectious than unvaccinated individuals, consistent with a recent report examining Delta breakthrough infections 8 . However, we must emphasize that this difference is not statistically significant, potentially due to both the relatively small number of samples from vaccinees and the fact that only 6 out of 12 individuals included in the vaccinated group were fully vaccinated at the time of enrollment.…”
Section: Main Textsupporting
confidence: 88%
“…17,[27][28][29][30] In addition, vaccinated individuals with a breakthrough infection are less infectious than unvaccinated individuals. 31 The particles emitted by these individuals might be less infectious through induction of antibodies that can coat the virus, which, through steric hindrance or complement fixation, can prevent virions from infecting susceptible hosts. The extent of vaccine-induced transmission blockade can be studied through contact-tracing studies comparing exposed, vaccinated with exposed, unvaccinated individuals.…”
Section: Effect Of Sars-cov-2 Vaccination On Host-to-host Transmissionmentioning
confidence: 99%
“…By responding and restricting viral infection within the first hours to days after exposure, cellular immunity can thereby reduce or even prevent symptoms of disease (i.e. preventing hospitalization and death) and potentially reduce the ability to spread virus to others ( 22 ).…”
Section: Introductionmentioning
confidence: 99%